ANALISIS EFISIENSI PEMANFAATAN PENDUDUK TERHADAP PENCIPTAAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) SETIAP KABUPATEN DI PROVINSI KALIMANTAN BARAT - B01109081, Santi AGNES (Jurnal Curvanomic, 2014)
This study aims to analayze the district / city the most efficientÂ  use of its human resources in the province of West Kalimantan, and to analyze teh efficiency of utilization of productive labor age and highly educated work force in creating a regional gross deomestic product. In order to obtain the result then examine some of the variables in the data thet the number of workers of childbearing age (15-64 years) per / district in western kalimantan in 2007-2012, data on the number of highly educated workers per district / citi in western borneo 2007-2012, the data of regional gross domestic product at constant prices of 2000 by country / city years 2007-2012, and gross domestic regional product data are created by highly educated workforce. Source of data used are secondary data. After analyzing the efficiency of utilization of the population towards the creation of regional gross domestic product every district in the province of west kalimantan obtained result is that the most efficient district in utilizing its human resources is the 2009-2012 pontianak city and country highway camps, as well as the utilization efficiency rate of population years 2007-2012 in western borneo fluctuated in the early years, but in the last 3 years, ie 2010-2012 and can be said to improve the situation efficiently create regional somestic product. Keywords: Gross Domestic Regional Product, Efficiency Utilization Of The Population.